Corporate Responsibility for Water Disclosure in Improving Environmental Transparency: A Case Study of ASEAN Countries - Putri, Tiara Tirta Andrissa; Wahyuningrum, Indah Fajarini Sri; Solikhah, Badingatus (Universitas Diponegoro, 2025)
This study analyzes water disclosures by leading ASEAN manufacturing firms regarding corporate social responsibility (CSR). The ASEAN region faces considerable environmental challenges, especially in managing water resources, which are increasingly critical owing to the rapid growth of manufacturing sector companies. Purposive sampling was used to analyze 176 secondary data units from sustainability and annual reports of companies listed on the stock exchanges of Indonesia, Malaysia, Singapore, Thailand, and the Philippines between 2020 and 2023. The variables studied include gender diversity, board meeting frequency, government ownership, profitability, and company size. The results show that only gender diversity significantly affects the exposure to water. Moderation regression analysis indicates that the CSR Committee strengthens the influence of company size but weakens the influence of other variables. This study makes a theoretical contribution by offering actual data on the intricate function of the CSR Committee in reducing the impact of corporate governance traits on water disclosure. The practical implication is that companies can improve the effectiveness of CSR committees, and the government can formulate policies that encourage sustainable water management through good corporate governance.